LOXL2 serves as a prognostic biomarker for hepatocellular carcinoma by mediating immune infiltration and vasculogenic mimicry. Issue 5 (May 2023) - Zhao, Nan; Chen, Chen; Guo, Yuhong; Liu, Tieju; Che, Na; Zhang, Danfang; Liang, Xiaohui; Zhang, Yanhui; Zhao, Xiulan
Abstract: Background: The development of human hepatocellular carcinoma (HCC) is a multistep process that is accompanied by progressive changes in the liver microenvironment, including immune evasion and angiogenesis. Lysyl oxidase-like 2 (LOXL2) has been suggested to contribute to tumour progression and metastasis; however, the underlying mechanism remains unclear. The purpose of the present study was to explore the relationship between LOXL2 and immune infiltration and vasculogenic mimicry (VM) and to identify the role of LOXL2 in HCC diagnosis prognosis evaluation. Methods: The Cancer Genome Atlas (TCGA), UALCAN, GEPIA and Kaplan–Meier plotter databases were used to analyse LOXL2 expression and perform survival analysis. The Tumour Immune Estimation Resource (TIMER) was used to analyse immune cell infiltration, immune cell biomarkers and immune checkpoints. Immunohistochemistry (IHC) of 201 HCC samples was used to confirm the expression of LOXL2 and its relationship with VM. Coimmunoprecipitation (co-IP) and gain- and loss-of-function studies were performed to confirm the molecular mechanism of LOXL2 in VM. Results: The expression of LOXL2 in HCC was higher than that in normal tissues at both the mRNA and protein levels. High expression of LOXL2 was associated with a poorer prognosis of HCC. The genetic alteration rate of LOXL2 was 5%. LOXL2 was positively related to immune cell infiltration and immune checkpoints (PD-1 and CTLA-4) in HCC. Co-IP showed that LOXL2 can interact directly with IQGAP1. Both gain- and loss-of-function studies showed that LOXL2 significantly induced cell migration, invasion and VM formation when IQGAP1 was upregulated. Conclusions: LOXL2 is involved in immune cell infiltration and promotes VM by upregulating IQGAP1. LOXL2 can be used as a novel biomarker for HCC diagnosis and prognosis prediction.